Momentum Effect Of Intellectual Capital On Corporate Valuation Of Oil And Gas - Ocheni, Stephen I. (Archives of Business Research, 2018)
The burgeoning fissure pragmatic amid market value and book value of myriad companies in the globe has haggard notice towards scrutinizing the value missing from financial statements. This is owed to the fact that intellectual capital (IC) shows a significant growing acceptance as a worthy topic of academic investigation and practical implication in the world. The study examines the momentum effect of intellectual capital on the corporate valuation of oil and gas companies of Nigeria. Secondary sources were explored in data collection while a regression model that aptly captures the relationship between the variables in data analysis to imprison the influence of Intellectual capital on corporate valuation in Nigeria. Furthermore, correlation analysis was applied in the assessment of the relationship between the intellectual capital and Nigerian corporate valuation. The outcome reveals that all the components of intellectual capital affect Nigeria corporate valuation. On the side of the relationship among the variables studied, the strength of their relationship is very high for all the variables. The researcher found that Intellectual capital has a positive impact on intellectual capital.Therefore; the study recommends that retention of intellects in Nigeria will be possible if an enabling business-friendly environment is provided